EDUCAÇÃO PARA O LAZER CIDADÃO: POLÍTICAS PÚBLICAS PARA A CIDADE DE SÃO LUÍS (MA) - Silva, Luiz Alfredo Ribeiro da (2006)
This work was developed in the city of capital São Luís of the State of Maranhão where the public politics of leisure still didn't get if it consolidates as a right of each citizen. It is a theoretical contribution developed starting from the legal point of view of the subject that bets the possibility of we use the Education in his/her wider sense as an I transmit effective for us to conquer the leisure citizen. It was looked for, then to understand the connection of this politics better, public with the leisure and viceversa, seeking to overcome the historical binomial of the sport and leisure and to bring for the center of the debate other possible interfaces, for the superbly of the inertia in that he/she is the leisure in our reality, as well as it supplies subsidies to help to understand the leisure in insured fundamental right for law to every Brazilian citizen. The present study had with hypothesis the following subjects: The current public politics implanted at the countries of advanced capitalism as in the outlying countries of capitalism, for they be anchored in the neoliberal conception, they are not indeed social politics; the inobservance and or ignorance of the existent legislation in the three extents of power, for they be not articulated have been hindering the formulation and implementation of effective public politics in the area of the leisure in our reality. The study also sought appears proposed of suspension of the current picture, starting from an inclusive action of the population the power publishes close to in the joint authors' condition of the it recounts that she intend to change.